Pemodelan Pola Aliran Fluida 2D di Area Panas Bumi Menggunakan Metode Elemen Hingga Pendekatan Galerkin - Samsul Bahri; Aditya Ramadhan (jcgant, 2022)
Indonesia is one of the countries with the largest geothermal potential in the world, reaching 40% of the world's potential. In geothermal areas there are several layers such as overburden, reservoirs, fractures and heat sources. Subsurface fluid flow patterns in geothermal areas are a topic that is often discussed, especially for exploration purposes. Fluid flow basically uses the principles of Darcy's law, the principle of continuity and the Navier-Stokes equation. In solving this equation, a numerical approach can be used, where the results are close to the actual value. The numerical method used in this study is the finite element method, where the geometric domain is divided into smaller domains. The shape of the two-dimensional elements used is a non-linear triangle. The purpose of this study is to describe the pattern of fluid flow in porous media, especially in the case of geothermal areas and to determine the effect of rock permeability anomalies on fluid flow patterns. The results of modeling with the finite element method show that rock permeability affects the pattern of fluid flow. Liquid will flow at a higher velocity to an area of higher permeability.